Analyzing First-Semester Students’ Speaking Performance Through Thematic Speaking Tasks - Manik, Ronika Apriyanti (Indonesian Research Journal on Education, 2025)
This study examined the speaking performance of first-semester EFL students with theme speaking tasks emphasizing pronunciation, fluency, and clarity. Thematic speaking tasks enabled learners to have authentic and purposeful communication, enabling teachers to evaluate oral production in authentic situations. The participants were asked to record their speaking with the theme given. Data were analysed descriptively with recorded one-minute speaking samples rated on a five-point scale. Most participants showed emerging control over pronunciation but all experienced challenges in articulatory accuracy, stress, and rhythm, influencing their fluency and message clarity. The participants also revealed hesitancy and lexical limitedness which points towards the initial stages of oral achievement. In terms of pedagogy, the results imply that students' pronunciation should be instructed with the integration of both segmental and suprasegmental aspects, whereas fluency should be developed via communicative and task-based practices. Shadowing, imitation, and lexical expansion can further enhance clarity-oriented activities towards achieving better intelligibility. In conclusion, thematic speaking activities are useful in identifying learners' oral competence and weakness and can be useful tools towards guiding pronunciation and fluency correction. Future studies should include a larger number, longer observation, and the incorporation of technology-assisted correction towards favoring sustained development in the domain of speaking.